Literature Review: Tinjauan Aspek Keamanan Dan Kerahasiaan Rekam Medis Di Ruang Filing - Winda Indri Anggraeni; Deasy Rosmala Dewi; Nanda Aula Rumana; Muniroh (SEHATMAS: Jurnal Ilmiah Kesehatan Masyarakat, 2022)
To maintain the security and confidentiality of patient medical records, a medical record storage room is required that meets the provisions in maintaining the security and confidentiality of medical records. This study aims to determine the security aspects in terms of physical, chemical and biological as well as the confidentiality aspects of medical records in the filing room. This study uses a literature review method with the PICO framework. Search articles using the Google Scholar database with keywords and Boolean operators in this study are "security" and "medical record confidentiality" and "filing". Research journal published in 2015–2020, in Indonesian, research design: using all research designs. The results of the study found security from the physical aspects that were most often found, namely the maintenance of the cleanliness of the filing room which was not maintained and the humidity temperature was less than optimal, the chemical aspect was that there were still officers eating and drinking in the filing room, the biological aspect of finding insects and pests. Meanwhile, from the aspect of confidentiality, there are officers other than medical records who enter the filing room.